THE ANALYSIS THERMAL CONDUCTIVITY OF PINEAPPLE FIBER COMPOSITES EPOXY AND NA2SIO3 AS CAR LIGHT SOCKET MATERIALS - Saputra, Eka Bima; Fachriza, Andry; Prabowo, Bambang; Hartono, Bibit (ROTOR, 2023)
Along with the increasing number of motorized vehicles and the massive renewal of it, their lifetime has become faster, especially for cars. The problem often occurs in cars that have passed their lifetime is a lighting system, one of which is that the car's light socket often melts. Car headlight sockets made of plastic and rubber which function as seals cause the socket to melt when exposed to heat. Based on the existing problems, the purpose of this research is to find new material for making car light sockets using the standard hot wire method. The production begins with mixing epoxy resin with hardener using the hand lay-up method with a ratio of 2:1. Stir mixture for 5 minutes and add the pineapple into molds (110x60x20) mm and wait for a day at room temperature. Furthermore, the thermal conductivity test using QTM-500 tester. Based on the research results, all specimens suitable for the requirements use as materials for making car light sockets, because the thermal conductivity values of all specimens (0.2231, 0.2061, 0.2249) W/mK were below the thermal conductivity values of the previous socket-making materials, 0.23 W/mK. The best specimen composition is specimen 1 with thermal conductivity value of 0.2231 W/mK. This is because specimen 1 has little porosity or voids and small conductivity value. Thus, the composition ratio that is best used in the manufacture of car light sockets based on the total mass of resin, hardener, pineapple fiber, and sodium silica is 15: 7.5: 1: 3.75. Keywords: composite, pineapple fiber, thermal conductivity, socket, catalyst